Deciphering the mystery of CHNG3 - Satoshi Narumi (Korean Society of Pediatric Endocrinology, 2024)
Congenital hypothyroidism (CH), characterized by insufficient thyroid hormone production due to abnormalities in the hypothalamic-pituitary-thyroid axis, is the most common congenital endocrine disorder. We previously conducted comprehensive genetic screening of 102 patients with permanent CH born in Kanagawa Prefecture, Japan and identified mutations in several genes in 19 CH patients, including defects in genes encoding dual oxidase 2, thyroglobulin, thyrotropin receptor, thyroid peroxidase, and paired-box 8. Despite these findings, approximately 80% of cases remain unexplained. CH pedigrees unexplained by known genetic forms of CH have been reported in the literature and registered as congenital hypothyroidism, nongoitrous, 3 (CHNG3; %609893) in Online Mendelian Inheritance in Man. We also identified a Japanese pedigree of CH that was compatible with CHNG3. However, the exact genetic cause of CHNG3 was not revealed by standard analysis methods such as exome sequencing and array comparative genomic hybridization. We therefore took a combined approach and analyzed a total of 11 undiagnosed CH pedigrees by whole genome sequencing to analyze a 3-Mb linkage region, and found a disease-causing variant affecting a TTTG microsatellite in a noncoding region on chromosome 15. Further analysis revealed that 13.9% of 989 Japanese CH patients had abnormalities involving the TTTG microsatellite, with a substantial proportion (41.5%) of familial CH cases carrying these mutations. Identification of the genetic cause of CHNG3 provides new insights into the pathogenesis of CH, and highlights the need for continued exploration of noncoding genomic regions in Mendelian disorders of unknown etiology.